In-Session Caregiver Behaviors during Evidence-Based Intervention Delivery for Children with ASD in Community Mental Health Services. Issue 1 (2nd January 2019) - Guan, Karen; Lau, Anna S.; Zhang, Aimee; Chlebowski, Colby; Haine-Schlagel, Rachel; Brookman-Frazee, Lauren
ABSTRACT: An Individualized Mental Health Intervention for Children with Autism Spectrum Disorder (AIM HI) is a collaborative, caregiver-mediated, and child-directed intervention for reducing challenging behaviors in children with autism spectrum disorder developed for delivery in community mental health programs. Using observational data from AIM HI sessions, the present study characterized the occurrence of 2 types of in-session caregiver behaviors: expressed concerns (i.e., expressing concerns about treatment strategies, expressing difficulty using skills, expressing difficulty completing homework) and participation engagement (i.e., asking questions, participating in session activities, showing commitment to therapy). Further analyses examined cultural differences in caregiver behaviors and associations between caregiver behaviors and clinician adherence. Participants included 39 caregiver–clinician dyads enrolled in a community effectiveness trial of AIM HI. Video recordings from 107 sessions during the first 2 months of treatment were coded for in-session caregiver behaviors and clinician adherence. Results indicated that expressed concerns were observed in 47% of the sessions. When controlling for household income, Latinx caregivers were rated lower for expressing concerns about treatment strategies and demonstrated lower participation engagement behaviors in session compared with non-Latinx White caregivers, suggesting that cultural factors may impact verbal engagement in sessions. Finally, expressing concerns about treatment strategies, expressing difficulty using skills, and participation engagement were positively associated with clinician adherence. Findings suggest that some expressed concerns and participation engagement behaviors may be indicators of positive caregiver engagement in the context of a collaborative intervention, and lower levels of such caregiver engagement may actually impede clinicians' delivery of intensive evidence-based intervention in routine care.